Edukasi Penggunaan Kosmetik di Kalangan Siswa Siswi SMA Muhammadiyah 3 Watukelir Sukoharjo - Meliana Novitasari; Kiki Puspitasary; Ani Nur Fauziah; Indarto Indarto; Dwi Joko Yuliyanto (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The use of cosmetics among high school students has become a necessity related to lifestyle. This trend is driven by the global beauty industry and the influence of social media exposure. Without adequate knowledge, however, it can lead to mistakes in selecting and using cosmetics. Therefore, this activity aims to increase the knowledge of high school students, especially those at Muhammadiyah 3 Watukelir Senior High School in Sukoharjo, regarding the use of cosmetics. The method used in this community service activity consists of four stages: preparation and coordination, implementation, delivery of education through PowerPoint presentations and brochures, evaluation and reporting. Both the pre-test and post-test included 10 questions summarizing the material presented. The post-test results showed a very significant increase in recognizing cosmetic expiration dates, rising from 77.9% in the pre-test to 100% in the post-test, an improvement of 22.1%. The increase in post-test scores indicates that this activity was successful.